Development of Academic Dashboard Application with Extreme Programming Method to Optimize Decision Making in Higher Education - Denny Jean Cross Sihombing (Jurnal Info Sains : Informatika dan Sains, 2023)
This research aims to investigate the development of an academic dashboard application using the Extreme Programming (XP) method as a response to digital transformation in higher education. Digital transformation presents opportunities and challenges in academic information management, requiring effective and responsive solutions. In this research, the academic dashboard application development approach integrates XP principles. The research method involves planning, design, coding, testing, delivery, and feedback. The results showed that the XP method provided responsiveness to changes, improved code quality, and improved application security. Thorough testing ensures the application is well-tested and can withstand diverse usage loads. The delivery phase ensures that each iteration meets user acceptance criteria. End-user feedback provides valuable insights for continuous improvement, which are integrated into the next iteration.